Insights Into Ferroptosis, a Novel Target for the Therapy of Cancer - Wang, Hong-Tao; Ju, Jie; Wang, Shao-Cong; Zhang, Yu-Hui; Liu, Cui-Yun; Wang, Tao; Yu, Xue; Wang, Fei; Cheng, Xue-Ru; Wang, Kun; Chen, Zhao-Yang (Frontiers in Oncology, 2022)
Ferroptosis is a new form programmed cell death with the characterized of excessive iron accumulation and subsequent unbalanced redox states. Ferroptosis is different from already reported cell death and has unique morphological features and biochemical process. Ferroptosis was first elaborated by Brent R. Stockwell lab in 2012, in which small molecules erastin and RSL3 induce cell death in Ras mutant cell lines. Ferroptosis involves in various physiological processes and occurrence of disease, especially shows strong potential in cancer treatment. Development of small molecule compounds based on the Stockwell’s research was found kill cancer cells, and some FDA-approved drugs were discovered which result in ferroptosis of cancer cells. Radiotherapy and checkpoint therapy have been widely used as a treatment for many types of cancer. Recently, some papers have been reported that chemotherapy, radiotherapy and checkpoint therapy induce ferroptosis of cancer cells, which provides new strategies for cancer treatment. Nevertheless, the limitless proliferation of tumor cells and the lack of cell death mechanisms are important reasons of drug resistance for tumor therapy. Therefore, we reviewed the molecular mechanism of ferroptosis and sensitivity to ferroptosis of different cancer cells and tumor treatment strategy.